Control Papers in Learning the Ukrainian Language for Professional Purpose at Medical University (Linguostylistic Studies, 2017)
The article highlights the value of control papers as kind of individual work in learning and teaching the Ukrainian Language (for Professional Purpose) for students of the Faculty of Pharmacy (correspondence form of training) at Higher Medical Educational Establishments. The emphasis is laid on the optimal tasks for medical students aimed at acquisition of knowledge of Ukrainian for professional purpose. The authors place importance on the following tasks as the most efficient: to reveal the essence of questions that provide consolidation of theoretical material knowledge on the indicated topic, to be able to analyze it, to compare and generalize studied information; to learn etiquette formulas and use them in future professional activity; to identify the phenomena of patronymic words in the professional language of medical worker; to write the bibliography according to the current standards; to write the definition, details and samples of documents; to choose correct equivalents to the language stereotypes, in which the norms are violated; orthographic tasks.
Keywords: control papers; tasks of control papers, individual work; tasks of control papers; individual work; the Ukrainian Language (for Professional Purpose); medical worker’s professional language